Typification of the name Erodium soluntinum Tod. (Geraniaceae) and its taxonomic implications - Domina, Gianniantonio; Scafidi, Filippo; Gargano, Maria Letizia (Phytotaxa, 2017)
The present contribution is part of the ongoing work promoted by the Italian Botanical Society aimed at recognizing and typifying all the taxa described from Italy and their loci classici, in order to increase their systematic knowledge and promote further studies (Domina et al. 2012, Peruzzi et al. 2015, Brundu et al. 2017). One of these taxa is Erodium soluntinum Todaro (1869: 36), a species belonging to Geraniaceae and considered an Italian endemic (Conti et al. 2005, Peruzzi et al. 2014, 2015). This name, as far as we are aware, is not yet typified.